S111. KOREAN MEDICATION ALGORITHM FOR BIPOLAR DISORDER: CHANGES IN PREFERRED MEDICATIONS FOR MANIA OVER 16 YEARS - Jon, Duk-In; Seo, Jeong Seok; Yoon, Bo-Hyun; Min, Kyung Joon; Bahk, Won-Myong (Schizophrenia bulletin, 2019)
Abstract Background Many treatment guidelines for bipolar disorders have been introduced to assist clinical decision. Majority of these guidelines are based on evidences from clinical trials. The Korean Medication Algorithm Project for Bipolar Disorder (KMAP-BP) was developed to adopt and maintain an expert-consensus paradigm which was more practical and specific to the atmosphere in Korea. In this research, preferred medication strategies for acute mania over four consecutively published KMAP-BP guidelines (2002, 2006, 2010, 2014, and 2018) were investigated. Methods The KMAP-BP questionnaire using a nine-point scale had covered some specific clinical situations divided into subsections with many treatment options. A written survey asked about the appropriateness of various treatment strategies and treatment agents commonly used by clinicians as the first-line. Results The most preferred initial treatment strategy for all subtypes of mania was a combination of mood stabilizer (MS) and atypical antipsychotic (AAP) in every edition. In contrast to MS monotherapy, the preference of combination therapy has been increased over time. Among MSs, lithium and valproic acid are almost equally preferred except in the mixed subtype where valproic acid is the most recommended MS. Carbamazepine was the first-line MS only in the first edition. Olanzapine, quetiapine, and aripiprazole were the preferred AAP for acute manic episode in later editions. This change might depend on the recent research results and safety profile. In cases of unsatisfactory response to the first-line medications, we recommended switching or adding another first-line agent. In KMAP-BP 2018, MS (more preferred as treatment of choice) or AAP monotherapy was first-line medication. Discussion The Korean experts have been increasingly convinced of the effectiveness of a combination therapy for acute manic episode. There have been evident preference changes: increased for AAP and decreased for carbamazepine.